MYC-activated CERS6-AS1 sponges miR-6838-5p and regulates the expression of RUBCNL in colorectal cancer: MYC-activated CERS6-AS1 sponges miR-6838-5p - Chen, Dong; You, Huiming; Xu, Xiaoping; Liu, Daocheng; Shen, Minmin; Pan, Yuan; Liu, Zhaohui; Zhang, Lei; Wang, Huijuan (Cellular and Molecular Biology, 2022)
As a leading gastrointestinal malignancy, colorectal cancer (CRC) is a serious threat to people’s health. A great amount of researches have elaborated that long non-coding RNAs (lncRNAs) play a key role in all kinds of tumors. In the current study, we mainly probed into the mechanisms of CERS6 antisense RNA 1 (CERS6-AS1) underlying CRC. For this purpose, the CERS6-AS1 expression level in CRC cells was disclosed by quantitative real-time PCR (qRT-PCR). In vitro and in vivo assays have validated the functional role of CERS6-AS1 in CRC. Mechanism assays were carried out to confirm the potential mechanism of CERS6-AS1 in CRC. Results showed that through experiments, we identified that the CERS6-AS1 expression level was up-regulated in CRC and the depletion of CERS6-AS1 hindered cell proliferative and migratory abilities and stimulated cell apoptotic levels in CRC. In addition, silencing of CERS6-AS1 repressed tumor growth. Moreover, CERS6-AS1 activated by MYC could sequestermiR-6838-5p, and then regulate rubicon-like autophagy enhancer (RUBCNL) expression level to influence the CRC cell proliferation, migration and apoptosis. In conclusion, The study focused on the MYC/CERS6-AS1/miR-6838-5p/RUBCNL axis was helpful for the potential diagnosis and standardized treatment of CRC.